2010
DOI: 10.1097/cad.0b013e328337f3e9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and inhibition of prostate and breast cancer growth by BGP-15, a new calcipotriene-derived vitamin D3 analog

Abstract: The role of vitamin D3 in cancer prevention and its potential as an anticancer therapeutic agent have been researched and are well established. However, the clinical use of the natural vitamin D3 metabolite, 1alpha,25-dihydroxyvitamin D3 [1,25(OH)2D3 or calcitriol] is limited by a possible cause of hypercalcemia and hypercalciuria. A new 24-chloro calcipotriene-based vitamin D3 analog (BGP-15) was synthesized and examined for antiproliferative activity in the androgen-dependent cell lines of prostate cancer (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Several other cell studies show 1,25(OH) 2 D or its analogs can induce apoptosis in prostate cancer cells (29, 30). These phenomena have also been seen in animal studies after treatment with vitamin D analogs, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Several other cell studies show 1,25(OH) 2 D or its analogs can induce apoptosis in prostate cancer cells (29, 30). These phenomena have also been seen in animal studies after treatment with vitamin D analogs, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…In vitro studies showed that this molecule may regulate cell differentiation and proliferation and exhibits growth-inhibiting effects against several human cancer cell lines including HL-60 and HL60/MX2 promyelocytic leukemia, U937 histiocytic lymphoma, MCF-7, T47D human breast cancer, HT-29 human colon cancer, and human SCC (Colston et al, 1992;Meephansan et al, 2012;Milczarek et al, 2013aMilczarek et al, , 2014. Regarding the possible mechanisms underlying the growth inhibiting and pro-differentiating effects of calcipotriol on tumor cells, in vitro studies highlighted the fact that a 20-h exposure of LNCaP prostate cancer cells and MCF-7 breast cancer cells to this analogue or to BGP-15, a new calcipotriene-derived vitamin D 3 analogue, generated procaspase-3 cleavage and ultimately, apoptosis (Berkovic et al, 2010). In addition, Wang et al (2010b) recently reported that calcipotriol significantly suppressed in vitro colon carcinoma cell invasion and enhanced the cytotoxicity of the anticancer regimen FOLFIRI (folinic acid, 5-FU, irinotecan) to cells in culture or in anchorage-independent growth.…”
Section: Calcipotriolmentioning
confidence: 99%
“…The vitamin D analog V decreases Bcl-2 expression in DU 145 cells [191]. Some calcitriol analogs have been shown to induce caspase-dependent apoptosis in several PCa cells [94,192]. Induction of apoptosis by calcitriol, however, appears to be cell-specific as it is not uniformly evident in all the cells that respond to calcitriol with growth inhibition.…”
Section: Apoptosismentioning
confidence: 98%